Economic Evaluation of Government Subsidy Program for Private Production of Primary Education in Lebanon: A Critical Review - Shakhnoza Shamsuddinova; Noor Un Nisa (Journal of Advanced Research in Social Sciences and Humanities, 2023)
Aim: Based on Barr’s conceptual paradigm of the welfare state and social justice in the context of education, the study aims to critically examine and highlight the significance of state involvement in primary education sector in case of Lebanon primary education infrastructure. Methodology: This paper adopted methodology to conduct methodical literature review of academic li terature, policy papers, and official reports in the field to partly explore the Lebanese government’s funding program for private education on the principles of efficiency and fairness. Findings: It has been determined that the most effective way to address inefficiency and fairness is for the government to subsidize commercial primary education output. Although the Lebanese government created a system of financing allowances to lessen parents’ financial strain in providing for their children’s education, the subsidy program has not succeeded in ensuring equitable access for the lowest rungs of society because there are still large disparities. In order to ensure more equal access to the funding scheme, the government should substitute the existing subsidy program with an income and needs-based funding allocation program, an example of which can be a constrained voucher scheme. Implications/Novel Contribution: The article provides a critical analysis and economic assessment of the Lebanese government’s primary education financing allotment program’s effectiveness and fairness. For policymakers to genuinely comprehend the issues and make informed decisions, the document offers in-depth knowledge about the subject.